Kondisi Lingkungan Rumah dan Perilaku Masyarakat Sebagai Faktor Risiko Kejadian Malaria di Puskesmas Benteng Bangka Belitung - Suwito, Suwito; Suhartono, Suhartono; Joko, Tri (Jurnal Kesehatan Lingkungan Indonesia, 2005)
ABSTRACT Backgroud: Bangka district is an endemic area of malaria, which has a relatively high incidence for malaria over the year. It has  clinical malaria rate  26.949 cases per year and Annual Malaria Incidence (AMI) 46,840/00. Benteng sub district is one of endemic area of malaria which has High Case Incidence (HCI) with 50,660/00 for AMI rate. This rate is higher compared to the national AMI (31,090/00 ). The aim of this research was to analyze the condition of the house and the community behavior as the risk factors of malaria at the workig area of Benteng Heath center in Bangka Belitung. Method: It was an observational research using case control design. The Subject of the research was categorized into two groups:  Case was someone who suffered malaria confirmed by the laboratory examination, and Control was someone who did not suffer malaria. The matching of case and control based on the consideration for sex and  age (maximum 3 years different). Result: The result of the research showed that risk factors of malaria are the habits not using mosquito coils with OR = 12,4 (CI 95% OR: 1,3 -13,18), bushes with OR = 7,3 (CI 95% OR:1,50 - 35,38), no predatory fish for larva with OR = 4,2 (CI 95% OR: 2,28-66,91), not using mosquito nets while sleeping with OR = 3,5 (CI 95% OR: 1,24 - 10,11). Conclusion: Environmental condition as risk factors in this research is the bushes around the house predatory fish in poonds and the habit of using mosquito coils as behaviour factors. Key words :   Physical house condition, community behavior, risk factors of  malaria.